2015
DOI: 10.1016/j.ijrefrig.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two-phase suction, liquid injection and two-phase injection for decreasing the discharge temperature of the R32 scroll compressor

Abstract: R32 has been considered as an important alternative in the phase-out of hydrochlorofluorocarbons (HCFCs) due to its advantages such as relatively low global warming potential compared to R410A, favorable thermal properties. However, the increased discharge temperature of the R32 compressor, compared with R410A, is the main barrier affecting the wide and quick adoption. In this work, three promising methods to decrease the discharge temperature of R32 scroll compressor, namely, two-phase suction, liquid injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Shuxue et al (2013) quantified the discharge temperature reduction by the use of enhanced vapor injection between 10 and 20 K but Xu et al (2013) only measured energy performance improvement using this configuration at non-extreme cooling and heating conditions. Yang et al (2015) concluded that two-phase injection outperforms liquid injection ( Figure 11) and two-phase suction in both cooling capacity and COP by 12% and 5%. Contrary to other synthetic refrigerants, the use of IHX in R32 systems is not recommended because it reduces the COP and increases the discharge temperature (Park et al, 2015).…”
Section: Single Split Air Conditioning Systems Containing Less Than 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Shuxue et al (2013) quantified the discharge temperature reduction by the use of enhanced vapor injection between 10 and 20 K but Xu et al (2013) only measured energy performance improvement using this configuration at non-extreme cooling and heating conditions. Yang et al (2015) concluded that two-phase injection outperforms liquid injection ( Figure 11) and two-phase suction in both cooling capacity and COP by 12% and 5%. Contrary to other synthetic refrigerants, the use of IHX in R32 systems is not recommended because it reduces the COP and increases the discharge temperature (Park et al, 2015).…”
Section: Single Split Air Conditioning Systems Containing Less Than 3mentioning
confidence: 99%
“…Barve and Cremaschi, 2012 Park et al, 2015Qv et al, 2017Shuxue et al, 2013Wu et al, 2016Xu et al, 2013Yang et al, 2015Zilio et al, 2015…”
Section: R32mentioning
confidence: 99%
“…In fact, an overly high discharge temperature and pressure of R32 under extremely high temperature conditions was a concern for the safe operation of the unit, and might be a concern for the compressor lifetime cycle; in addition, it has been the main barrier for the wide and quick introduction of this fluid in air conditioning systems where R410A has typically been used, as shown in Figure 6. Yang et al [59] proposed different cycles with modifications to reduce the discharge temperature. A two-phase injection outperforms a liquid injection and two-phase suction in terms of the cooling capacity and COPc by 12% and 5%, respectively, and significantly decreases the discharge temperature of the R32 scroll compressor (benefited by its significant amount of latent heat).…”
Section: Performance and Discharge Temperature Concern Of Pure R32mentioning
confidence: 99%
“…For two‐phase injection, it is currently rarely studied because of test difficulties in metering injection mass flow rate . Yang experimentally demonstrated that three injection styles, ie, two‐phase suction injection, direct liquid injection, and two‐phase injection, obviously decreased the T d of the compressor, and the cooling capacity and COP with two‐phase injection were 11.8% and 4.8% higher than those with the other two injection styles, respectively. Kim et al built a mathematical model to forecast the influence of the liquid, vapor, and two‐phase injection on the heat pump performance.…”
Section: Introductionmentioning
confidence: 99%